2018
DOI: 10.3390/antibiotics7040097
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Programmes in Community Healthcare Organisations in England: A Cross-Sectional Survey to Assess Implementation of Programmes and National Toolkits

Abstract: Objective: The aim of this study was to assess antimicrobial stewardship activities in Community Healthcare Organisations (CHOs) with focus on the implementation of the two national antimicrobial stewardship toolkits, TARGET (Treat Antibiotics Responsibly, Guidance, Education, Tools) and SSTF (Start Smart, then Focus). The study utilised a web-based survey comprising 34 questions concerning antimicrobial policies and awareness and implementation of antimicrobial stewardship toolkits. This was distributed to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This increase could be due both to the overuse of antimicrobials in patients with severe COVID-19 [6], as well as to the interruption of antimicrobial stewardship programs because of the redeployment of personnel to other areas. In fact, several antimicrobial stewardship activities have been stopped during the pandemic, mainly because of the reduction in available resources, as reported in a survey conducted among 95 healthcare facilities in the United Kingdom [13]. However, few data are available on the effect of this interruption.…”
Section: Discussionmentioning
confidence: 99%
“…This increase could be due both to the overuse of antimicrobials in patients with severe COVID-19 [6], as well as to the interruption of antimicrobial stewardship programs because of the redeployment of personnel to other areas. In fact, several antimicrobial stewardship activities have been stopped during the pandemic, mainly because of the reduction in available resources, as reported in a survey conducted among 95 healthcare facilities in the United Kingdom [13]. However, few data are available on the effect of this interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many participants (40.6%) strongly believed that 'adequate training should be provided to community pharmacists on antimicrobial use,' which shows a positive perception of participants regarding ASPs. Many studies have already demonstrated that ASPs are vital for reducing antimicrobial substitution [35][36][37][38]. It is, therefore, critical for the government to accelerate the implementation of ASPs in community settings.…”
Section: Discussionmentioning
confidence: 99%
“…A further quantitative delity analysis utilized attendance lists, checklists, worksheets, exit surveys and expert observations to allow a sophisticated view on a team-based, behavioral intervention in care aids [50]. Focusing on rational antibiotic prescribing efforts, research on antimicrobial stewardship (AMS) programs in British community healthcare organizations was applied by a web-based survey strategy to gain insights about the engagement in introduced stewardship toolkits being a part of a ve-year crossgovernmental awareness strategy [51]. In a cluster randomized controlled trial which aimed to promote AMS among British community pharmacies to improve the management of respiratory tract infections, an accompanied process evaluation was conducted [52] in a cross-sectional survey design based on the COM-B (capability, opportunity, motivation and behavior) model [53].…”
Section: Discussionmentioning
confidence: 99%